2020
DOI: 10.7759/cureus.10448
|View full text |Cite
|
Sign up to set email alerts
|

Manganese, a Likely Cause of 'Parkinson's in Cirrhosis', a Unique Clinical Entity of Acquired Hepatocerebral Degeneration

Abstract: With idiopathic Parkinson's disease being a common entity, parkinsonism in acquired hepatocerebral degeneration (AHD) in the context of Manganese (Mn) has gained importance in recent years. An insight into the pathomechanisms behind this disease has been put forth. How can Mn as a divalent metal exert its effect in leading to chronic neurodegenerative disorder? Secondary to decreased excretion in liver cirrhosis, Mn significantly alters the striatal dopaminergic system. Management of this debilitating disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…According to our findings, haloperidol‐induced PD was associated with significant fibrous tissue deposition, representing Ishak score 3, and significantly increased levels of two key fibrosis markers; TGF‐β the strongest inducer of fibrotic diseases and hydroxyproline, a main collagen constituent that acts as a good extracellular matrix accumulation marker 20 . In accordance, a positive correlation between PD and liver dysfunction was perceived in various clinical studies that confirmed an association between PD and cirrhosis 42–44 . In addition, liver impairment and liver enzymes abnormalities were found to exist in patients with PD 45 .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…According to our findings, haloperidol‐induced PD was associated with significant fibrous tissue deposition, representing Ishak score 3, and significantly increased levels of two key fibrosis markers; TGF‐β the strongest inducer of fibrotic diseases and hydroxyproline, a main collagen constituent that acts as a good extracellular matrix accumulation marker 20 . In accordance, a positive correlation between PD and liver dysfunction was perceived in various clinical studies that confirmed an association between PD and cirrhosis 42–44 . In addition, liver impairment and liver enzymes abnormalities were found to exist in patients with PD 45 .…”
Section: Discussionsupporting
confidence: 77%
“… 20 In accordance, a positive correlation between PD and liver dysfunction was perceived in various clinical studies that confirmed an association between PD and cirrhosis. 42 , 43 , 44 In addition, liver impairment and liver enzymes abnormalities were found to exist in patients with PD. 45 PD‐associated hepatic fibrosis may be a consequence of brain V A deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a retrospective cohort study of various types of hepatitis reported increased rates of subsequent PD in individuals with hepatitis B and hepatitis C [50]. Growing evidence suggests that the prevalence of liver disease history among PD patients is connected to the inability of the liver to clear the blood of neurotoxins like α-syn and manganese (Mn), which can then accumulate in the liver [51,52]. Compromised hepatic ability resulting from liver disease may sabotage the removal of pathological proteins, allowing neurotoxins to enter cerebral circulation and facilitate PD pathogenesis [52].…”
Section: Possible Role Of Liver In Pdmentioning
confidence: 99%
“…Growing evidence suggests that the prevalence of liver disease history among PD patients is connected to the inability of the liver to clear the blood of neurotoxins like α-syn and manganese (Mn), which can then accumulate in the liver [51,52]. Compromised hepatic ability resulting from liver disease may sabotage the removal of pathological proteins, allowing neurotoxins to enter cerebral circulation and facilitate PD pathogenesis [52]. The entrance of toxic substances into the brain is further provoked by portosystemic shunting, which often occurs as a result of advanced liver diseases like acquired hepatocerebral degeneration (ADH) [52].…”
Section: Possible Role Of Liver In Pdmentioning
confidence: 99%
“…Magnesium deficiency occurs due to the malabsorption of magnesium in the small intestine, is exacerbated by diuretic use, and is correlated with diminished muscle strength and reduced cognitive ability in adults with cirrhosis [32]. Elevated manganese levels in patients with cirrhosis have been related to selective manganese accumulation in the basal ganglia, resulting in extrapyramidal and neuropsychiatric symptoms [33]. Specific evidence regarding the advantageous impact of micronutrients and vitamin supplementation in cirrhotic patients is not available.…”
Section: Micronutrients Metabolismmentioning
confidence: 99%